Investigation of physico – chemical, physical properties and moisture content studies of soil using organic amendment - Jeyaseeli, P.; Jeyamangalam, F.; Selvaraj, S.; Vella Durai, S. C. (International Journal of Agricultural Technology, 2021)
The organic farming custom of crop revolution keeps safety and well-bring attribution of soils. The behavior of soil Physico-chemical properties, physical properties, and moisture content during the organic farming regularity were investigated. The treated soils were analyzed in a soil testing chemistry laboratory. The soil fertility is replenished by improving the physical properties such as bulk and particle densities, water holding capacity, saturated moisture, hydraulic conductivity, pore space, and permeability for suitable organic amendment. Physico-chemical properties of electrical conductivity and pH levels reduced more than the control plot, then the available nitrogen, phosphorus, and potassium are increased. For the amended plot with less pH values, it indicated that the soil was good for farming practices. Organic farming would increase the small nutrients such as nitrogen, phosphorus and potassium within the sandy loam soil for crop production.The observed physical properties such as bulk density, particle density decreased more than the control plot, so that the plants in cultivated soil would better root growth and high crop yields. The water holding capacity, pore space, saturated moisture content, hydraulic conductivity, permeability, and porosity increased more than the control plot. The soil before and after harvest, the physical properties such as the field capacity, wilting point and the moisture content increased more than the control plot